2019
DOI: 10.3892/ol.2019.9904
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the differentially expressed microRNAs in esophagus squamous cell carcinoma of Kazakh patients in Xinjiang

Abstract: Despite improvements in diagnosis and treatment, the survival of patients with advanced stages of esophageal squamous cell carcinoma (ESCC) remains poor. Therefore, novel biomarkers that can assist with early detection of ESCC are required. In the present study, three paired ESCC and normal esophageal tissue samples from Xinjiang Kazakh patients were obtained and microRNA (miRNA) microarray analysis was used to detect the differentially-expressed miRNAs. The target genes of the identified miRNAs were predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Both our study and a previous study found that miR-1224-5p was downregulated in ESCC 24 . Our present data indicated that its low expression was significantly associated with shorter survival time of ESCC patients.…”
Section: Discussionsupporting
confidence: 81%
“…Both our study and a previous study found that miR-1224-5p was downregulated in ESCC 24 . Our present data indicated that its low expression was significantly associated with shorter survival time of ESCC patients.…”
Section: Discussionsupporting
confidence: 81%
“…A quantitative real-time PCR analysis reported that hsa-miR-760 is significantly downregulated in ESCA tissues and cell lines, suggesting that this miRNA could be used as a prognostic indicator [57] . Significant differential expression of hsa-miR-769-5p was observed in ESCA tissue when compared to the normal tissues [58] . Over-expression of hsa-miR-1301-3p induces cell proliferation and tumorigenesis in gastric cancer tissues [59] .…”
Section: Resultsmentioning
confidence: 91%
“…Additionally, has-miR-1290 is the main up-regulated miRNA that potentially targets ACTR3, MYH11, and YWHAZ. A recent report shows that has-miR-5580-3p is down-regulated in OSCC samples, esophagus squamous cell carcinoma tissues and colorectal cancer compared with healthy control (Wang et al, 2017;Chamorro-Petronacci et al, 2018b;Cheng et al, 2019). Has-miR-1290, which is one of the most frequently and consistently up-regulated miRNAs in human cancer, has been suggested as crucial drivers for tumor initiation and cancer progression (Zhang et al, 2016), and play an oncogenic role in cellular processes of esophageal squamous cell carcinoma (ESCC) (Li et al, 2015).…”
Section: A) B)mentioning
confidence: 99%